Aplicación del cuestionario multidimensional del impacto de la evaluación de riesgo de cáncer (MICRA), en una muestra española - Cruzado, Juan A.; Pérez Segura, Pedro; Sanz, Ruth (Psicooncología, 2005)
It is studied the psychosocial impact of Counselling Genetic Oncology (CGO) on the participants who have received the genetic test results. A sample of 59 participants that had undertaken genetic testing and received results was assessed by The Multidimensional Impact of Cancer Risk Assessment (MICRA) Questionnaire.It was studied possible differences in psychosocial impact according to: result type of, previous oncologist diagnosis, time passed from result communication and type of hereditarysyndrome. The outcomes showed that GCO does notproduce negative psychosocial impact. There were not differences by previous diagnosis,time communication and type of hereditary syndrome on MICRA. It is necessary more research for Spanish MICRA adaptation with the purpose to dispose of a specific instrument effective for psyhosocial impact study of genetic testing.